A influência da regulação emocional dos pais no desenvolvimento infantil dos filhos: diferenças por gênero parental. - Maffazioli, Ana Carolina (2020)
Child development is greatly influenced by the regulators present in the child's life, who usually to be the parents during the early childhood. Therefore, an adequate parenting is very important to ensure the child development. Although it has not yet be